Evaluation of magnetic carriers employed for immobilization of lipase from candida rugosa - Otávio Domingues; Letícia Karen dos Santos; Rondinelli Donizetti Herculano; Danilo Luiz Flumignan; Ariela Veloso de Paula (The Journal of Engineering and Exact Sciences)
Currently, the use of magnetic nanoparticles has aroused interest in industrial processes, and the combination of their properties with the immobilization of lipases has been developed in order to produce carriers of easy separation of the reaction medium. In this context, the objective of the present study was to immobilize Candida rugosa lipase in magnetic nanoparticles, such as magnetite and maghemite, by physical adsorption and covalent bonding. The biocatalysts were evaluated by infrared spectroscopy (FTIR) and hydrolytic activity analysis. Thus, from the analyses performed, the best biocatalyst obtained was the immobilized by covalent bond in maghemite, presenting a hydrolytic activity of 174.67 U/g.